Socio-demographic profile of teenage mothers in Spain - Hernández-Cordero, Ana Lucía; Gentile, Alessandro; Tanase, Elena Luminita (Acciones e Investigaciones Sociales, 2019)
In this paper we describe the evolution of teenage maternity and early pregnancies in Spain from the mid-1990s until 2017. Thanks to the examination of secondary data from national surveys and the handling of findings from a large body of research carried out prior to our own, we draw attention to the sexual and affective behaviours of adolescents residing in this country and take a closer look at the socio-demographic profile of those girls that have given birth before the age of 20 during this period.